INCREASING POPULARITY OF INDIAN MUSIC THROUGH MEANS OF COMMUNICATION IN THE ERA OF GLOBALIZATION: वैश्वीकरण के युग में संचार साधनों के माध्यमों से भारतीय संगीत की बढ़ती लोकप्रियता - Verma, Vinita (International Journal of Research -GRANTHAALAYAH, 2015)
How far our forefathers were, it shows that, the importance of globalization, which the people of the rest of the world are able to understand today, has been determined by our mystics very early on that the concept of "Vasudhaiva Kutumbakam" of our culture Formed the basis. At present, the whole world is like a village due to technological development and communication revolution in the whole world, because the means of communication have added so much that the whole world has been reduced to a few steps and a few hours, and the world wide The process of K has accelerated the westernization process. हमारे पूर्वज कितने दूर दृष्टा थे, यह इस बात का द्योतक है कि, जिस वैश्वीकरण के महत्व को शेष विश्व के लोग आज समझ पाये हैं, उसे हमारे मनीषियों ने बहुत पहते ही निर्धारित कर ‘‘वसुधैव कुटुम्बकम्’’ की अवधारणा को हमारी संस्कृति का आधार बनाया। वर्तमान समय में सम्पूर्ण विश्व में हुए तकनीकी विकास एवं संचार क्रान्ति के कारण समस्त विश्व ही एक ग्राम के समान है, क्योंकि संचार साधनों ने इसे इतना जोड़ दिया है कि पूरी दुनिया ही चंद कदमों एवं कुछ घंटों की दूरी में सिमट गई है और विश्व व्यापीकरण की प्रक्रिया से पश्चिमीकरण प्रक्रिया में तेजी आई है।